2021
DOI: 10.3390/cells10071632
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Regulates Tumor Progression and Tumorsphere Formation by Suppressing PD-L1 Expression in Non-Small Cell Lung Cancer (NSCLC) Cells

Abstract: Recently, natural compounds have been used globally for cancer treatment studies. Silibinin is a natural compound extracted from Silybum marianum (milk thistle), which has been suggested as an anticancer drug through various studies. Studies on its activity in various cancers are undergoing. This study demonstrated the molecular signaling behind the anticancer activity of silibinin in non-small cell lung cancer (NSCLC). Quantitative real-time polymerase chain reaction and Western blotting analysis were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…Previous studies have demonstrated that UA can induce cell cycle arrest and apoptosis in several cancer types [ 31 33 ]. ROS generation tremendously plays an important role in the anticancer activity of a natural compound [ 34 ]. We found that UA treatment elevated the expression of iNOS at the transcriptional and translational levels so that iNOS induction leads to ROS generation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that UA can induce cell cycle arrest and apoptosis in several cancer types [ 31 33 ]. ROS generation tremendously plays an important role in the anticancer activity of a natural compound [ 34 ]. We found that UA treatment elevated the expression of iNOS at the transcriptional and translational levels so that iNOS induction leads to ROS generation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MSM can induce mitochondrial apoptosis against various cancer types [ 31 , 32 ]. ROS generation plays a vital role in the anticancer activity of a natural compound [ 39 ]. We found that MSM elevated the expression of iNOS at the transcriptional and translational levels so that iNOS induction leads to ROS generation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, Silibinin, as the antioxidant compound, characterizes oxidative stress parameters in a rat model of oxaliplatin-induced neuropathy. Additionally, the hepatoprotective effects ( Loguercio and Festi, 2011 ) as well as the anticancer activity ( Rugamba et al, 2021 ; Zhou et al, 2021 )cooperatively impart silibinin a ubiquitous profile that distinguishes the compound from other antioxidant agents used clinically for the treatment of oxaliplatin-induced neuropathy.…”
Section: Plant-derived Medicines Limiting Platinum-induced Peripheral Neurotoxicitymentioning
confidence: 99%